An Analysis of Relationship Between the Learning Organization and Organization Culture in Indian Business Organization - Singh, Kavita (Organizations and Markets in Emerging Economies, 2010)
To keep pace with the rapid changes in the environment, organizations must keep pace, otherwise they are likely to perish. They have to remain flexible and continually improve to gain competitive advantage and must be able to adapt and strive to take the lead, otherwise their survival will be at stake. To meet the challenges posed by this rapidly changing environment, an organization must create and assimilate new knowledge at an increasing pace, encourage innovation and learn to compete in new ways. The culture of the organization plays a very significant role in keeping the process of learning vibrant in the organization leading it to become a learning organization. The present paper identifies the relationship between the organization culture and the learning organization in Indian business organizations and concludes that the organization culture plays a vital role in the development of a learning organization. It further contends that three major constructs of organization culture, i.e., openness, proaction and experimentation tend to provide the members of an organization with a sense of direction and creative thinking which in turn enhance organizational learning in turbulent environment.
Keywords: learning organization; organization culture; openness; proaction; experimentation